Cultural tourism in the wake of web innovation emerging research and opportunities - McDonald, J. Scott; Bennett, John R.; Merwin, Keith A.; Merwin, Gerald A. (IGI Global, 2019)
"This book examines the revolutionary changes taking place in the field cultural tourism resulting from application of web-based and other information technologies"--Provided by publisher